(untitled) (The Peerian Journal, 2024)
Educational software and the possibilities of using it in practice provide an opportunity to go one step further in the educational process and increase the effectiveness of teaching. The information technology of education refers to special technical media (computer, audio, film, video). all technologies used are understood. In the period when computers began to be widely used in education, the term "new information technologies of teaching" appeared, in general, any pedagogical technology is information technology, because the technological basis of education is information and its movement, therefore, from the computer it is more appropriate to call the teaching technology used computer technology.